Adäquatheit und Äquivalenz - Reiss, Katharina (HERMES - Journal of Language and Communication in Business, 1989)
The science of translation theory, like any other science, is in need of specific terminology which is commonly accepted as regards definition and content description. Translation theory very often makes use of two concepts, in particular: "Adäquatheit" and "Äquivalenz", though without defining these terms in an unambiguous way. This paper attempts to delimit one concept in relation to the other and to provide definitions accordingly.